History and Characteristics of Hadith Madrasa in The Sam Region During the Narration Period - Haifa Hanifah; Badri Khaeruman (Prodi Ilmu Hadis Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2023)
Hadith scholars in Sham have distinctive characteristics compared to others, such as Makkah, Kufah, or Egypt. This is inseparable from the historical background behind the spread of hadith in this region and the war conflicts, which impact the stagnation of the recording of hadith, which is developing rapidly. The main objective of this study is to reveal the characteristics of the hadith madrasa in Sham. The method used is qualitative, in which documents are described and then analyzed, either by comparison with other papers or by developing a transmission model. Sham's hadith scholar was born when the embryo of recording hadiths began to be echoed, so many of the sahabah who recorded hadiths, Sham's hadith scholars, were known for their thorough nature. They were cautious in narrating hadiths where the hadith scholars of Sham had adopted the sighatul ada' method in the tahammul wa al-ada' hadith process. The strongest sanad in terms of 'ittishal' in Syria is al-Auza'i [157 H], from Hasan Athiyah al-Muhāribī Abū Bakr al-Dimasqī [120 H], because the narrators in the sanad this goes beyond the standards set by the muddy. The implications of this research are expected to be able to develop hadith studies, especially those related to regional hadith studies